INTEGRASI NILAI-NILAI PANCASILA DALAM KURIKULUM INTERNATIONAL BACCALAUREATE (IB) DI SEKOLAH DASAR INTERNATIONAL - Nabella Widya Natasia; Nirva Diana; Muhammad Muchsin Afriyadi (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study examines the integration of Pancasila values within the International Baccalaureate (IB) curriculum at the primary education level and its implications for students’ character development. Employing a Systematic Literature Review (SLR) guided by PRISMA protocols, this study synthesizes findings from 10 peer-reviewed articles retrieved from Google Scholar, Scopus, and Semantic Scholar. The results reveal that Pancasila values are embedded through inquiry-based and transdisciplinary pedagogies, as well as co-curricular and extracurricular practices that promote experiential and reflective learning. Core values—including cooperation, tolerance, responsibility, and social justice—are consistently aligned with key attributes of the IB Learner Profile, such as caring, principled, and open-minded. This conceptual alignment enables a coherent integration of national identity within a global curriculum framework. The findings further indicate that such integration contributes significantly to the development of students’ socio-emotional competencies and 21st-century skills. However, the implementation remains constrained by structural and pedagogical challenges, including limited teacher capacity, the absence of standardized integration frameworks, and instructional time constraints. This study contributes to the literature by offering a synthesized conceptual mapping between Pancasila values and IB educational principles, while highlighting the need for systematic instructional design and institutional support to ensure sustainable and contextually grounded character education in globally oriented curricula. ABSTRAK Penelitian ini bertujuan untuk menganalisis integrasi nilai-nilai Pancasila dalam kurikulum International Baccalaureate (IB) pada jenjang sekolah dasar serta implikasinya terhadap pembentukan karakter peserta didik. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA melalui penelusuran artikel pada basis data Google Scholar, Scopus, dan Semantic Scholar. Dari hasil seleksi diperoleh 10 artikel yang relevan untuk dianalisis. Hasil penelitian menunjukkan bahwa integrasi nilai-nilai Pancasila dilakukan melalui pembelajaran berbasis inquiry, pendekatan transdisipliner, serta kegiatan kokurikuler dan ekstrakurikuler. Nilai-nilai utama yang terintegrasi meliputi gotong royong, toleransi, tanggung jawab, dan keadilan sosial. Selain itu, terdapat kesesuaian antara nilai-nilai Pancasila dengan karakter dalam IB Learner Profile, seperti caring, principled, dan open-minded. Integrasi tersebut terbukti memberikan dampak positif terhadap pembentukan karakter peserta didik, termasuk peningkatan sikap sosial dan kompetensi abad ke-21. Namun demikian, implementasi masih menghadapi kendala, seperti keterbatasan kompetensi guru, kurangnya panduan operasional, serta keterbatasan waktu pembelajaran. Oleh karena itu, diperlukan strategi integrasi yang lebih sistematis dan dukungan institusional untuk mengoptimalkan penerapan nilai-nilai Pancasila dalam kurikulum IB di sekolah dasar.